Augmented reality for inclusive growth in education: the challenges - Kezia Herman Mkwizu; Ritimoni Bordoloi (AAOU Journal)
Purpose – Inclusive growth in the education sector is still a major challenge in some countries because of limited access to technologies and internet connectivity, among other reasons. However, as a technology, augmented reality (AR) is expected to be widely used in the field of education in the future. The main purpose of this paper is to explore the use of AR for inclusive growth in education as well as identify the challenges, particularly in countries like India and Tanzania. Design/methodology/approach – This paper applies a systematic literature review by analysing and synthesising relevant documents, mainly journal articles, books and conference papers. Descriptive statistics and cross-tabulation were used for the analysis. Content analysis was used to evaluate the contents of the reviewed literature. Findings – For the use of AR, it is important to have adequate digital infrastructure, access to universal internet or broadband facilities and the digital empowerment of citizens. Major challenges to inclusive growth in education include the lack of trained teacher educators and students’ preference for practical or project-based curriculum. Practical implications – Practitioners in both countries may consider the use of AR for inclusive growth in education. Originality/value – This paper specifically examines the use of AR in higher education and the related challenges based on a review of two countries, namely India and Tanzania.